2007
DOI: 10.1074/jbc.m608627200
|View full text |Cite
|
Sign up to set email alerts
|

Trivalent Recognition Unit of Innate Immunity System

Abstract: Ficolins are a kind of pathogen-recognition molecule in the innate immune systems. To investigate the discrimination mechanism between self and non-self by ficolins, we determined the crystal structure of the human M-ficolin fibrinogen-like domain (FD1), which is the ligand-binding domain, at 1.9 Å resolution. Although the FD1 monomer shares a common fold with the fibrinogen ␥ fragment and tachylectin-5A, the Asp-282-Cys-283 peptide bond, which is the predicted ligand-binding site on the C-terminal P domain, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
66
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 64 publications
(72 citation statements)
references
References 54 publications
6
66
0
Order By: Relevance
“…The amino acid sequence of FD1 is 49% and 45% identical to that of the FBG domain of tachylectin-5A and the human fibrinogen fragment, respectively. The crystal structure revealed that the hydrophobic side-chains of Phe127 and Leu128 are important for trimer formation by FD1 (Tanio et al, 2007). Indeed, the replacement of Phe127 with Thr in FD1 drastically decreased the monomer-monomer interaction in solution, as judged by a dynamic light-scattering experiment (data not shown).…”
Section: Trimeric Structure Of Fd1mentioning
confidence: 97%
See 4 more Smart Citations
“…The amino acid sequence of FD1 is 49% and 45% identical to that of the FBG domain of tachylectin-5A and the human fibrinogen fragment, respectively. The crystal structure revealed that the hydrophobic side-chains of Phe127 and Leu128 are important for trimer formation by FD1 (Tanio et al, 2007). Indeed, the replacement of Phe127 with Thr in FD1 drastically decreased the monomer-monomer interaction in solution, as judged by a dynamic light-scattering experiment (data not shown).…”
Section: Trimeric Structure Of Fd1mentioning
confidence: 97%
“…2a). The ligand-binding study of FD1 in solution revealed that the ligand-binding site is located near the Ca 2+ binding site, the Cys270-Cys283 disulfide bond, and an unidentified group with a pK a of 6.2 (Tanio et al, 2007). The group with a pK a of 6.2 was tentatively assigned to His284.…”
Section: Trimeric Structure Of Fd1mentioning
confidence: 98%
See 3 more Smart Citations